Implementation of the Remap-CIRC Learning Model Toward High School Students’ Learning Outcomes in Acid–Base Topics - Agusto Jeremia Giawa; Sukemi Sukemi; Agung Rahmadani; Indah Lestari (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Maritim Raja Ali Haji, 2026)
Students’ difficulty in understanding abstract and complex acid-base concepts requires the implementation of appropriate learning strategies. This study aims to evaluate the effectiveness of the Reading Concept Map-Cooperative Integrated Reading and Composition (REMAP-CIRC) learning model in improving students’ learning outcomes on acid-base topics. This research employed a pre-experimental method using a one-group pretest–posttest design. The participants consisted of 33 eleventh-grade students (Class XI-4) enrolled in the science track at State Senior High School 17 Samarinda during the 2024/2025 academic year. Data were collected through pretest and posttest instruments, as well as student response questionnaires. The data were analyzed using the Wilcoxon test to determine significant differences between pretest and posttest scores. The results showed that the average student score increased from 28.18 (pretest) to 73.64 (posttest). The N-Gain value was 0.61, categorized as moderate, while the effect size was 3.14, indicating a very high effect. In addition, the student response questionnaire showed a positive response with an average percentage of 79.84% (good category). Based on these results, it can be concluded that the REMAP-CIRC learning model is effective in improving students’ learning outcomes on acid-base topics.